SISTEM PEMANTAUAN DAN KEAMANAN PADA TOKO BERBASIS MIKROKONTROLER ESP32 DEVKIT V1, ESP32 CAM AI THINKER, SENSOR AM312 DAN BUZZER BERBASIS IOT - Ramadhan, Diaz; Hakim, Abdul; Irawati, Diyah Ruri (Journal of Information System, Informatics and Computing, 2025)
In today's digital era, security systems integrated with Internet of Things (IoT) technology offer modern solutions to protect assets and property. This research aims to design and implement an IoT-based security system using the ESP32 DevKit V1 microcontroller, ESP32 Cam, AM312 sensor, and a buzzer. The system detects motion using the AM312 sensor, which triggers the ESP32 Cam to capture images and send them to the Telegram application, while also enabling the activation of the buzzer via Telegram commands to enhance security. After testing, the AM312 sensor was able to detect motion at distances of 2 to 4 meters, but was ineffective at 6 meters. The system successfully sent real-time images through the ESP32 Cam when motion was detected and responded to buzzer activation commands via the Telegram bot. This system allows shop owners to monitor their store remotely using mobile devices and receive real-time notifications.